RELIEF DEVELOPMENT OF THE BABIA GÓRA MASSIF, WESTERN CARPATHIAN MOUNTAINS - Łajczak, Adam (Quaestiones Geographicae, 2014)
The paper discusses structural considerations relating to landform development on Mt. Babia Góra (1,725 m a.s.l.), the highest massif in the flysch section of the Western Carpathian Mountains. The Babia Góra massif consists of folded Palaeogene-age sediments, including resistant Magura sandstone and less resistant sub-Magura layers, with numerous tectonic faults. The area has inverse-type geomorphology. The monoclinal ridge of the massif itself consists of the resistant Magura sandstone dipping southwards. Since the Miocene, the development of the massif’s relief has involved a number of processes, including: tectonic uplifting, removal of a thick layer of rocks, exposure of sub-Magura layers over a large area, the staged development of valleys dissecting the pediments surrounding the ever higher ridge, and slope retreat due to deep landsliding. Axes of linear terrain forms, escarpments of landslide scars and of headwater areas follow two main intersecting fracture lines present within the massif. Large quantities of colluvial material are transported away from the massif along these lines. The development of the land relief has led to the elongation of slopes as local elevation differences increased. Landsliding has developed in an uphill direction, which means that the youngest relief is observed on the highest sections of steep slopes. The development of the massif’s northern slope, which has formed a high and precipitous cuesta, began to accelerate only after a nearly complete exposure of the sub-Magura layers at its foot. Following this exposure the profile of the massif’s N-S cross-section has begun to become asymmetrical. With time, the degree of general remodelling of the massif has tended to decrease. As a result, the geomorphological contrast between the northern and southern sides of the massif has become well established. The description of the probable development of the Babia Góra relief is based on the author’s fieldwork, an analysis of geological maps and aerial photos, and on literature.